Do Consumers Really Follow a Rule of Thumb? Three Thousand Estimates from 130 Studies Say "Probably Not" - Tomas Havranek; Anna Sokolova (Charles University in Prague, Institute of Economic Studies (IES), 2016)
We show that three factors combine to explain the mean excess sensitivity reported in studies estimating consumption Euler equations: the use of macro data, publication bias, and liquidity constraints. When micro data are used, publication bias is corrected for, and the households under examination do not face liquidity constraints, the literature implies no evidence for the excess sensitivity of consumption to income. Hence little remains for pure rule-of-thumb behavior. The results hold when we control for 45 additional variables reflecting the methods employed by researchers and use Bayesian model averaging to account for model uncertainty. The estimates of excess sensitivity are also systematically affected by the order of approximation of the Euler equation, the treatment of non-separability between consumption and leisure, and the choice of proxy for consumption.
Keywords: C83; D12; E21; 330; excess sensitivity; rule-of-thumb consumers; liquidity constraints; publication bias; Bayesian model averaging